The Role of Consumer Satisfaction in Mediating The Relationship Between E-sercive Quality and Customer Commitment Among Link Aja Applocation Users in Denpasar City - Dewi, Ni Kadek Setia; Meryawan, I Wayan; Handayani, Made Mulia (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
The degradation of consumer behavior who are committed to digital wallet applications is influenced by the dissatisfaction felt due to the weak quality of electronic services. A mismatch between expectations and services can cause consumers to move to other platforms that are considered to better meet their needs and wants. This study aims to prove the role of user satisfaction in mediating the relationship between e- service quality and customer commitment in LinkAja application users in Denpasar City. This study uses an associative quantitative approach, where data is collected through filling out questionnaires that are distributed to be filled out by 110 users of the LinkAja application in Denpasar City. Samples were taken by purposive sampling method and data analysis was done using Structural Equation Modelling (SEM) which was operated using Smart PLS. The findings of the research prove that e- service quality has a significant positive effect on customer commitment and consumer satisfaction, consumer satisfaction has a significant positive effect on customer commitment and plays a role as a partial mediator. Improving the quality of digital services (e-service quality) has been proven to be able to increase consumer satisfaction while building a stronger customer commitment to the company.